Communication for HIV/AIDS Prevention in Kenya: Social-Cultural Considerations - Muturi, Nancy W. (My University, 2010)
The acquired immune deficiency syndrome (AIDS) epidemic is spreading fast in Africa in spite of the various efforts and resources put in place to prevent it. In Kenya, reproductive health programs have used the mass media and other communication interventions to inform and educate the public about the disease and to promote behavior change and healthy sexual practices. This effort has led to a discrepancy between awareness and behavioral change among people of reproductive age. In this article I examine the discrepancy in Kenya from a communications perspective addressing social cultural and related factors contributing to the lack of change in behavior and sexual practices. I draw on the theoretical framework of Grunig’s model of excellence in communication, the importance of understanding and relationship building between programs and their stakeholders. Data were gathered qualitatively using focus groups and in-depth interviews among men and women in rural Kenya. Key findings indicate that although awareness of sexually transmitted diseases (STDs) including human immunodeficiency virus (HIV)/AIDS is high in Kenya, a majority of the population, particularly those in the rural communities, lack understanding of the communicated messages. They also lack the knowledge of other ways of transmitting HIV particularly among those not sexually involved. Cultural beliefs, values, norms, and myths have played a role in the rapidly increasing epidemic in the rural communities and yet HIV/AIDS communication programs have not addressed these factors adequately. I conclude that successful behavior change communication must include strategies that focus on increasing understanding of the communicated messages and understanding of the audience through application of appropriate methodologies. Building a relationship with the audience or stakeholders through dialogues and two-way symmetrical communication contributes toward this understanding and the maintenance of the newly adopted behaviors and practices.
Keywords: HIV/AIDS; Africa; Mass media; Behavior; Sexual practices; Cultural beliefs